STASIUN KERETA API PEMATANG SIANTAR: PERAN, DAMPAK, DAN TANTANGAN SELAMA PANDEMI COVID-19 - Sitompul Rikardo; Rana Alif Novandi; Lila Pelita Hati; Peninna Simanjuntak (Bajang Institute, 2024)
Railway stations have an important role in facilitating public transportation, including in Pematang Siantar City, North Sumatra. Siantar Station, which was established in 1915, serves not only passengers but also freight/logistics. However, the Covid-19 pandemic presented serious challenges to the station, with a decline in passenger numbers and revenue, as well as the need to implement strict health protocols. This research uses interviews and historical writing methods to examine the impact of Covid-19 on Siantar Station and its surrounding community. The results show that Siantar Station is experiencing a significant economic impact, while still striving to maintain a safe and efficient service. The station has a complex influence on the surrounding community, with social, economic and health impacts that need to be considered. With good coordination between the station, local government, and the community, Siantar Station is expected to continue to contribute positively to the common welfare